Peran Self-Efficacy dalam Efektivitas Pembelajaran Berbasis Teknologi: Sebuah Tinjauan Literatur Sistematis (SLR) - Prihatin; Dedi Kuswandi; Ika Andrini Farida (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2025)
Abstract: This study aims to analyze the role of self-efficacy in the effectiveness of technology-based learning through a systematic literature review designed to identify patterns, contributing factors, and pedagogical implications across studies. The research method involved selecting articles through a rigorous screening procedure using PRISMA standards, resulting in a set of relevant studies that were then thematically analyzed. The findings indicate that self-efficacy functions as a key psychological factor mediating the relationship between technology use and learning outcomes, particularly by enhancing motivation, engagement, persistence, and self-regulation. The development of self-efficacy is supported by the quality of digital learning design, structured success experiences, social support in the learning process, and learners’ technopedagogical competence. The study concludes that the effectiveness of technology-based learning does not depend on the platform used, but rather on learning experiences designed to foster learners’ confidence. It recommends strengthening instructional design, improving learner competence, and expanding research across different educational levels to deepen understanding of the role of self-efficacy in digital learning contexts.   Keywords: Self-Efficacy, Technology-Based Learning, Instructional Design, Learning Effectiveness, Educational Technology